Macromol. Chem. Phys. 8/2018. Issue 8 (19th April 2018) - Kondo, Mizuho; Makino, Kotaro; Miyake, Kazutoshi; Matsuo, Yoshiaki; Fukae, Ryohei; Kawatsuki, Nobuhiro
Abstract : Front Cover : In article number1700602 by Mizuho Kondo, Nobuhiro Kawatsuki, and co‐workers, photomobile liquid‐crystalline polymer films containing N ‐benzylideneaniline (NBA) as a mesogenic photoresponsive crosslinking point are fabricated. The film bends towards the actinic light source under UV irradiation due to the trans–cis photoisomerization of the NBA moiety, reverting to the initial shape when left in the dark.